Kontrol Perilaku, Komitmen Profesional, Religiusitas dan Niat Melakukan Whistleblowing - Putri, Selvi Aprilia; Zahroh, Fatmawati (E-Jurnal Akuntansi, 2022)
Failure to provide important information such as financial statements can cause harm to various interested parties. The study discusses what factors can affect an accountant's intention to take whistleblowing actions. The study used quantitative methods by distributing questionnaires to 40 employees of a public accounting firm in Malang. Data analysis using IBM SPSS 26 using multiple linear regression analysis. The results of the analysis show that behavioral control and professional commitment have no effect on an accountant's intention to take whistleblowing actions. While religiosity has a positive and significant effect on an accountant's intention to take whistleblowing actions. Keywords: Behavioural Control; Professional Commitment; Religiosity;  Whistleblowing.